Trial protocol of an open-label pilot study of oral naltrexone–bupropion combination pharmacotherapy for the treatment of methamphetamine use disorder (the NABU trial) - Jonathan Brett; Paul S Haber; Nicholas Lintzeris; Didier Jutras-Aswad; Nadine Ezard; Brendan Clifford; Krista J Siefried; Adrian John Dunlop; Liam Acheson; Carl Moller; Michael Christmass; Kirsten Morley; et al. (BMJ Open)
Introduction Methamphetamine use disorder is a global public health concern with no approved pharmacotherapies for its treatment. One recent randomised controlled trial conducted in the USA examined a combination of bupropion and naltrexone not readily available globally. Here, we report a trial protocol for an oral formulation of combined naltrexone and bupropion.Methods and analysis This single-arm, open-label pilot study will assess the safety and feasibility of oral naltrexone and bupropion (40 mg/450 mg daily in divided doses) in adults with methamphetamine use disorder. Participants (n=20) will be outpatients of a stimulant treatment program at an inner-city hospital in Sydney, Australia. The primary endpoint is Day 84. Participants will attend weekly study visits from Baseline to Week 12 and a follow-up telephone visit at Week 16. All participants will receive treatment as usual, such as psychosocial therapy. Primary outcomes are safety (measured by treatment-emergent adverse events (AEs)/adverse reactions) and feasibility (measured by the time taken to recruit, the proportion of ineligible participants, retention in the study and study medication adherence). Secondary outcomes will assess methamphetamine use, craving and withdrawal; treatment goals and expectations; physical and psychological well-being; depression and anxiety; and treatment satisfaction. Qualitative interviews will assess the acceptability of the intervention and outcome measures.Ethics and dissemination This study received ethics approval from the St Vincent’s Hospital Human Research Ethics Committee (2023/ETH00549). Results will be submitted to peer-reviewed journals and scientific conferences, and a video abstract will be created to ensure that the findings are accessible to participants and people who use methamphetamines.Trial registration number ANZCTR: ACTRN12623000866606 (protocol V.2.1 dated 08 April 2024).